2017
DOI: 10.1073/pnas.1708873114
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of microbial filter feeding

Abstract: Microbial filter feeders are an important group of grazers, significant to the microbial loop, aquatic food webs, and biogeochemical cycling. Our understanding of microbial filter feeding is poor, and, importantly, it is unknown what force microbial filter feeders must generate to process adequate amounts of water. Also, the trade-off in the filter spacing remains unexplored, despite its simple formulation: A filter too coarse will allow suitably sized prey to pass unintercepted, whereas a filter too fine will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 34 publications
6
78
1
Order By: Relevance
“…The swimming speeds we calculated for slow and fast swimmers ( figure 3) fall within the For the flagellar kinematics of a typical S. rosetta choanoflagellate, we calculated the inward flux during one beat cycle to be approximately 19.01 mm 3 for a slow swimmer and 15.76 mm 3 for a thecate cell tethered mid-water, which produces clearance rates (volume flow rate through the capture zone) of 461.84 mm 3 s 21 and 383.01 mm 3 s 21 , respectively, at the beat frequency of 24.3 Hz. These are at the low end of clearance rates reported for other species of choanoflagellates by Nielsen et al [25], some directly measured and some estimated using published experimental data, between 400 mm 3 s 21 and 4400 mm 3 s 21 .…”
Section: Comparison Of Model Predictions With Datamentioning
confidence: 64%
See 2 more Smart Citations
“…The swimming speeds we calculated for slow and fast swimmers ( figure 3) fall within the For the flagellar kinematics of a typical S. rosetta choanoflagellate, we calculated the inward flux during one beat cycle to be approximately 19.01 mm 3 for a slow swimmer and 15.76 mm 3 for a thecate cell tethered mid-water, which produces clearance rates (volume flow rate through the capture zone) of 461.84 mm 3 s 21 and 383.01 mm 3 s 21 , respectively, at the beat frequency of 24.3 Hz. These are at the low end of clearance rates reported for other species of choanoflagellates by Nielsen et al [25], some directly measured and some estimated using published experimental data, between 400 mm 3 s 21 and 4400 mm 3 s 21 .…”
Section: Comparison Of Model Predictions With Datamentioning
confidence: 64%
“…Their model included a representation of the cell body, the collar of microvilli and the undulatory flagellum. Their results suggested that a thin cylindrical flagellum could not account for experimentally measured water fluxes, and they proposed that the flagellum of this species has a broad vane [25]. Another earlier computational study of choanoflagellate hydrodynamics, using a regularized Stokeslet framework, modelled the effect on the flow of a lorica, a basket-like structure that is not present in the S. rosetta cells considered here [26].…”
Section: Hydrodynamics Of Choanoflagellatesmentioning
confidence: 95%
See 1 more Smart Citation
“…One of the most beautiful examples, which also highlights the importance of multicellular cooperation, is the rosette structure in many species of choanoflagellates [96]. These free-living cell groups generate dipolar flows [97,98] when not sessile and also accumulate as carpets on surfaces [99], acting like aggregate random walkers [100]. To our knowledge, the idea that accrued groups of such organisms could optimise the attraction of nutrients collectively has not been explored much in the current literature.…”
Section: A Gradients In Swimmer Density or Activity Itselfmentioning
confidence: 99%
“…Organisms that increase in size may extend ( partly) out of the boundary layer, ensuring that at least part of their surface is exposed to regions of high mixing. Behavioral adaptations to life in the boundary layer include the generation of jets (Santhanakrishnan et al, 2012), the use of cilia or flagella to create local flows (Petersen, 2007;Nielsen et al, 2017), or any other behavior resulting in increased fluid mixing and thus local reduction in boundary layer thickness.…”
Section: Introductionmentioning
confidence: 99%